Non-market values of water sensitive urban designs: a case study on rain gardens - Iftekhar, Md. S.; Zhang, F.; Polyakov, M.; Fogarty, J.; Burton, M. (Elsevier, 2021)
Rain gardens are an established element of water sensitive urban infrastructure. However, information on people's preferences for such systems is lacking. To understand whether people express willingness to pay for such systems and whether estimates are transferable between locations, we conducted choice experiments in Sydney and Melbourne. We found that people are willing to pay for rain gardens. The marginal willingness to pay for different features is similar in both locations, but the transfer of compensating surplus values between locations still generates transfer errors. The implications of transfer errors are investigated using a benefit-cost analysis of a rain garden installation.